Impact of Islamic Spiritual Guidance on the Resilience of Covid-19 Patients - Baderun, Nadzmi Akbar; Fuadi, Anwar; Hidayat, Taufik; Rani, Samsul (Alhadharah: Jurnal Ilmu Dakwah, 2024)
The Covid 19 pandemic has caused serious problems, especially patients who have become restless, restless, anxious and don't know what to do, even to the point of despair. At that time, spiritual guidance is needed so that patients have self-resilience, so that Covid 19 patients have the ability to survive and rise in the face of their illness. The aim of this research is to find out about Islamic spiritual guidance services and their influence on increasing the resilience of Covid 19 patients. This research method uses quantitative methods, using simple linear regression analysis. The analysis requirements are to test the correctness of the data, and test the homogeneity of the variables to be tested. In this research, it was found that Islamic spiritual guidance services have an effect on increasing the resilience of Covid 19 patients. Spiritual guidance services can increase the resilience of Covid 19 patients, because the service makes them calm and strong in illness, creates enthusiasm to face illness, expresses the meaning of life's trials with words that are simple and easy to understand, make sure the patient is able to bear the burden of illness as a trial from God, provide spiritual guidance for recovery.